Alcohol Use and HIV Disease Progression in an Antiretroviral Naive Cohort. (15th April 2018) - Hahn, Judith A.; Cheng, Debbie M.; Emenyonu, Nneka I.; Lloyd-Travaglini, Christine; Fatch, Robin; Shade, Starley B.; Ngabirano, Christine; Adong, Julian; Bryant, Kendall; Muyindike, Winnie R.; Samet, Jeffrey H.
Abstract : Background: Alcohol use has been shown to accelerate disease progression in experimental studies of simian immunodeficiency virus in macaques, but the results in observational studies of HIV have been conflicting. Methods: We conducted a prospective cohort study of the impact of unhealthy alcohol use on CD4 cell count among HIV-infected persons in southwestern Uganda not yet eligible for antiretroviral treatment (ART). Unhealthy alcohol consumption was 3-month Alcohol Use Disorders Identification Test—Consumption positive (≥3 for women, ≥4 for men) and/or phosphatidylethanol (PEth—an alcohol biomarker) ≥50 ng/mL, modeled as a time-dependent variable in a linear mixed effects model of CD4 count. Results: At baseline, 43% of the 446 participants were drinking at unhealthy levels and the median CD4 cell count was 550 cells/mm 3 (interquartile range 416–685). The estimated CD4 cell count decline per year was −14.5 cells/mm 3 (95% confidence interval: −38.6 to 9.5) for unhealthy drinking vs. −24.0 cells/mm 3 (95% confidence interval: −43.6 to −4.5) for refraining from unhealthy drinking, with no significant difference in decline by unhealthy alcohol use ( P value 0.54), adjusting for age, sex, religion, time since HIV diagnosis, and HIV viral load. Additional analyses exploring alternative alcohol measures, participant subgroups, and time-dependent confounding yielded similar findings. Conclusion: Unhealthy alcohol use had no apparent impact on the short-term rate of CD4 count decline among HIV-infected ART naive individuals in Uganda, using biological markers to augment self-report and examining disease progression before ART initiation to avoid unmeasured confounding because of misclassification of ART adherence.